The determinants of cleaner energy innovations of the world's largest firms: the impact of firm learning and knowledge capital*. Issue 4 (19th May 2017) - Laurens, Patricia; Le Bas, Christian; Lhuillery, Stéphane; Schoen, Antoine
ABSTRACT: In this paper, we address the determinants of clean energy inventions by 946 large firms. We use a new set of large firms' patent portfolios and we broaden and deepen existing literature on this issue in two main ways: first, we conduct our study directly at the firm level and not at the industry or national levels and second, we do not focus on a single industry but encompass all industrial sectors. Drawing on firm (internal and external) knowledge and knowledge accumulation, we show there is a robust positive association between the (past) knowledge accumulated capital related to clean technologies and the number of inventions produced in that field, even after controlling for industry and nation fixed effects and other factors. The same relation works for (past) knowledge-accumulated capital in other (non-clean) technologies. However, the relation's impact on the number of clean inventions produced is much lower. The magnitudes of our coefficient are in line with that obtained previously on firms in the auto-industry or at the sectoral level.